2021
DOI: 10.2147/cpaa.s327541
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Thrombocytosis Associated with Enoxaparin Therapy in an Adolescent

Abstract: Secondary thrombocytosis, often referred to as a reactive thrombocytosis, is more common than primary thrombocytosis and has many potential etiologies including anemia, infection, inflammation, medications, and post-splenectomy. When considering the critically ill patient in the ICU setting potential medication-related etiologies of thrombocytosis should be included in the differential diagnosis. We present a 15-year-old adolescent with a traumatic brain injury who developed thrombocytosis that was temporally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Clemens Stockklausner et al reported that the most common causes were infections (49.5%), postsplenectomy (7.8%), Kawasaki disease (6.4%), tissue damage (4.5%), blood diseases (3.7%), malignancies (3.7%), renal diseases (3.2%), chronic inflammation (1.8%), essential thrombocythemia (0.5%), and other causes (3.7%) 10 . In some other studies, the frequencies of infections in secondary thrombocytosis were 39, 53, 30, and 63%, respectively 11 14 . In our study, infections (37.9%) were also the most common cause of secondary thrombocytosis in accordance with the previously published studies.…”
Section: Discussionmentioning
confidence: 76%
“…Clemens Stockklausner et al reported that the most common causes were infections (49.5%), postsplenectomy (7.8%), Kawasaki disease (6.4%), tissue damage (4.5%), blood diseases (3.7%), malignancies (3.7%), renal diseases (3.2%), chronic inflammation (1.8%), essential thrombocythemia (0.5%), and other causes (3.7%) 10 . In some other studies, the frequencies of infections in secondary thrombocytosis were 39, 53, 30, and 63%, respectively 11 14 . In our study, infections (37.9%) were also the most common cause of secondary thrombocytosis in accordance with the previously published studies.…”
Section: Discussionmentioning
confidence: 76%
“…The use of EX both in prophylactic and therapeutic management is slowly becoming the procedure of choice in paediatric patients, and is increasingly recommended in newborns due to its easy dosing, low number of complications and rare interactions with other drugs and nutrients [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The use of EX, like other LMWHs, is slowly becoming the treatment of choice in paediatric patients and is increasingly recommended in newborns. LMWHs have an advantage over non-fractionated heparin (NFH) due to easier monitoring, fewer complications and less frequent interactions with other drugs and nutrients [29,30].…”
Section: Frequency Of Coagulation Parameters Monitoringmentioning
confidence: 99%
See 1 more Smart Citation